Patient-Centered Care - Hari Kusnanto (Faculty of Medicine, Public Health, and Nursing, 2018)
..........In the context of patient services constrained by cost barriers, physicians often find it unfavorable to choose an option that prioritizes patient interest. As has been the practice of physicians since Hippocrates, physicians position themselves as the one who best knows what is the most appropriate for the patient. This is in contrary to the concept of patient-centered care. Supported by the ethical principle of patient autonomy, patient-centered services / PCC (LBP/Layanan Berpusat Pasien) empower patients through the provision of more clear and accurate information, allowing patients to be partners in decision-making concerning their health........The cultural shift and the way services are delivered to the patients must be designed, managed and rewarded financially. Patients are no longer merely customers who receive services, but partners in the process of prevention and cure of the disease. The expected benefits of patient-centered services are greater patient and family satisfaction, increased reputation of the physician or the health care provider institution, increased morale and clinical productivity of supporting staffs, and cost savings and service efficiency.......